Corporate Governance Country Assessment : Republic of Peru - World Bank (Washington, DC, 2013)
This report assesses the corporate governance policy framework, and enforcement and compliance practices in Peru. Corporate governance reform is at an early stage, and some legislation has recently been upgraded to protect shareholder rights. The major issues are driven by the growing importance of private pension funds, which have become the most important institutional investors. At present, the governance structure of the pension fund administrators is weak, and there are not enough checks and balances to deal with conflicts of interest. Improving the internal governance structure is crucial in order to ensure the preservation of private savings for retirement. Voting and board representation policies are being developed by the regulator, so that pension funds can assume an active role as shareholders of their portfolio companies. The report recommends that: (1) the procedures governing the general meetings should be amended to encourage shareholder participation; (2) the related party transactions' approval process should be more transparent and allow shareholders to opt to challenge transactions that are unfair to them; (3) the thresholds to challenge corporate decisions should be lowered and harmonized for all listed companies, and (4) there should be a requirement for a minimum number or percentage of independent directors on the boards of listed companies and for the creation of audit committees, and (5) directors should have access to adequate training so as to understand their duties and responsibilities. The report also proposes increased independence and a strengthening of enforcement mechanisms for the securities regulator.